Pedagogia de projetos: avaliação de método para alunos sob um sistema de educação inclusiva - Melo, Fernanda Passarini (2018)
Our country's official assessments, presented by Ideb (Basic Education Development Index), have demonstrated unsatisfactory school performance rates. The percentage of school dropouts and functional illiterate students at the end of middle and high school has increased every year, demonstrating a certain inefficiency on current Brazilian educational system. Brazilian educational system has been through some changes, but it continues to be a somewhat archaic and monopolized system, that is, only the teacher is the holder of knowledge and power. Many educators have made changes, such as Paulo Freire, who inserted his method of literacy based on the previous knowledge of the student; however, schools still demonstrate non-expressive changes and a high rate of failure. Taking this into account, there are studies of different methodologies, which go on the opposite way to our current educational system. These are methodologies that focus on the total learning of the student, such as, Escola da Ponte, in Portugal. Objective: To present positive results in the school performance of a control group of students; a case with Down Syndrome and a case with learning difficulties in linguistic intelligence, specifically on writing; all occurring in an elementary and high school, in the city of São José do Rio Preto - SP. This school has a differentiated pedagogical system; it uses the pedagogy of projects in its methodology, that is, the studies are made from the interest of each student, thus making it more motivating. Method: This is a qualitative and quantitative, prospective historical field work. Teaching-learning reports were analyzed to certify the effectiveness of the methodology adopted by the school. Results: All the students have demonstrated development by means of the reports and notes. Conclusions: The results are intended to aid on the development as well as the contribution to improve the educational system of the public and private network, since it could be properly modified and the student should be the center of the teaching-learning process.